Some aspects of application of pesticides and fertilizers on nutritive value and other characteristics of crop plants - Nikolić, Bogdan; Waisi, Hadi; Đurović, Sanja; Dugalić, Miloš; Jovanović, Vladan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
We surveyed different aspects of the application of agrochemicals (pesticides and foliar non-standard fertilizers) on the nutritive value and other non-yield characteristics of crop plants. The survey was based on results of our own trials and studies conducted by other researchers. Various parameters of plant and seedling growth, and yield, were analyzed, as well as the chemical composition, and energetic and thermodynamic parameters of plants in order to better assess the impact of these agrochemicals on crops. The application of various agrochemicals has been found to affect the germination of seeds produced by treated plants. The most significant and most diverse results have been obtained by analyzing the yield and yield components of many different crops (field crops, fruits, vegetables), as well as their chemical composition (mineral elements, different sugars, secondary metabolites, etc.) in terms of improving their nutritive quality. It was found that in maize seedlings it occurs by changing the content of various elements, as well as polyphenol profiles and thermodynamic parameters, and the effects did not only depend on the dosage of agrochemicals but also on maize genotype. We also found that agrochemicals affected the energetic and thermodynamic parameters of individual maize plants, as well as the parameters of plant growth and yield. It was noticed that these agrochemicals greatly affected the content of microelements, starch and crude proteins in maize and barley, sugar and polyphenol contents in various fruit trees and soybean. We noted that in certain agroecological situations these agrochemicals have led to spectacular magnification of yields of different crops, but there were also situations when they did not have any positive effect on crop yield, which is discussed also in the context of results of other researchers.